Arterial resection during pancreatectomy for pancreatic cancer: a systematic review and meta-analysis - Mollberg, Nathan; Rahbari, Nuh Nabi; Koch, Moritz; Hartwig, Werner; Hoeger, Yumiko; Büchler, Markus W.; Weitz, Jürgen (Annals of surgery, 2011)
Background: - The majority of pancreatic cancers are diagnosed at an advanced stage. As surgical resection remains the only hope for cure, more aggressive surgical approaches have been advocated to increase resection rates. Institutions have begun to release data on their experience with pancreatectomy and simultaneous arterial resection (AR), which has traditionally been considered a general contraindication to resection. The aim of the present meta-analysis was to evaluate the perioperative and long-term outcomes of patients with AR during pancreatectomy for pancreatic cancer. - Methods: - The Medline, Embase, and Cochrane Library and J-East databases were systematically searched to identify studies reporting outcome of patients who underwent pancreatectomy with AR for pancreatic cancer. Studies that reported perioperative and/or long-term results after pancreatectomy with AR were eligible for inclusion. Meta-analyses included comparative studies providing data on patients with and without AR and were performed using a random effects model. - Results: - The literature search identified 26 studies including 366 and 2243 patients who underwent pancreatectomy with and without AR. All studies were retrospective cohort studies and the methodological quality was moderate to low. Meta-analyses revealed AR to be associated with a significantly increased risk for perioperative mortality [Odds ratio (OR) = 5.04; 95% confidence interval (CI), 2.69-9.45; P < 0.0001; I2 = 24%], poor survival at 1 year (OR = 0.49; 95% CI, 0.31-0.78; P = 0.002; I2 = 35%) and 3 years (OR = 0.39; 95% CI, 0.17-0.86; P = 0.02; I2 = 49%) compared with patients without AR. The increased perioperative mortality (OR = 8.87; 95% CI, 3.40-23.13; P < 0.0001; I2 = 5%) and lower survival rate at 1 year (OR = 0.50; 95% CI, 0.31-0.82; P = 0.006; I2 = 40%) was confirmed in the comparison to patients undergoing venous resection. Despite substantial perioperative mortality, pancreatectomy with AR was associated with more favorable survival compared with patients who did not undergo resection for locally advanced disease. - Conclusions: - AR in patients undergoing pancreatectomy for pancreatic cancer is associated with a poor short and long-term outcome. Pancreatectomy with AR may, however, be justified in highly selected patients owing to the potential survival benefit compared with patients without resection. These patients should be treated within the bounds of clinical trials to assess outcomes after AR in the era of modern pancreatic surgery and multimodal therapy.
Gesehen am 01.09.2022